AI-driven online adaptive radiotherapy in prostate cancer treatment: considerations on activity time and dosimetric benefits - Francesco Preziosi; Althea Boschetti; Francesco Catucci; Claudio Votta; Luca Vellini; Sebastiano Menna; Flaviovincenzo Quaranta; Elisa Pilloni; Andrea D’Aviero; Michele Aquilano; Carmela Di Dio; Martina Iezzi; et al. (Radiation Oncology)
Abstract Aims Recent advances in Radiotherapy have led to the development of online adaptive RT (oART), a procedure addressing inter-fraction anatomical variations. Integrating artificial intelligence (AI) into the oART procedure speeds up the process and reduces user dependency. This study investigates the dosimetric advantage of implementing AI-driven oART in prostate cancer. Methods A total of 31 prostate cancer patients treated with oART on an AI-integrated Linac were analyzed. Patients were categorized by nodal involvement. For prostate-only cases, the Clinical Target Volume (CTV) included the prostate and seminal vesicles (CTV1), with a 5 mm margin (8 mm caudally) for Planning Target Volume (PTV), named PTV1. For nodal cases, pelvic lymph nodes were added (and categorized as CTV2) with a 5 mm isotropic margin (PTV2). Daily CBCTs were acquired, with OARs (rectum, bladder, bowels) automatically segmented by the AI system, while targets were manually delineated. Two plans were generated: a predicted one, calculating the original plan’s fluence on daily anatomy, and an adapted one, with complete fluence re-optimization. Daily DVH indicators for PTV(V95%), CTV(D98%), bladder (V65Gy), bowel (V45Gy), and rectum (V50Gy) were compared between predicted and adapted plans using the Wilcoxon-Mann-Whitney test. Total session time, from CBCT acquisition to treatment completion, was also recorded. Results oART treatment improved prostate coverage in both patient groups (+10.4% and +11.8% in PTV V95% for patients with and without lymph nodes) and CTV D98% (+2.6% with lymph nodes, +2.9% without). Improvements for arm 2 were smaller (+3.1% in PTV2 V95%, +2.2% in CTV2 D98%). Statistical differences were insignificant in OAR DVH indicators (p > 0.1). Median treatment time was 25 min and 32 min for prostate-only and lymph node cases, respectively. Conclusion This study demonstrates that oART in prostate cancer results in a significant improvement in target coverage with no significant difference in OARs.